Physical Activity, Steps, and Cardiovascular Disease: A Literature Review - Giancarlo Saldana; Linda Liu; Charles A. German (Heart and Mind)
Despite decades of literature on the benefits of physical activity (PA) on cardiovascular disease (CVD) and other health outcomes, rates of physical inactivity and sedentary time remain alarmingly high and are likely contributing to the global increase in CVD. Roughly one-third of the world’s population does not meet the World Health Organization (WHO) guideline recommended levels of aerobic PA, defined as ≥ 150 min of moderate-intensity PA or ≥75 min of vigorous-intensity PA, or an equivalent combination of both. This is in addition to recommending individuals perform at least 2 days of muscle-strengthening activities per week involving all major muscle groups, which provide additional CVD benefits beyond aerobic PA. Disparities by sex and between high- and low-income countries persist, with modeling studies suggesting a direct global economic cost of $5 billion dollars. To combat the global health crisis of physical inactivity, the WHO implemented a global action plan on PA in 2013, which set a target of a 15% relative reduction in physical inactivity by 2030. Barriers to attaining adequate PA levels are abundant, however, step counting represents a relatively novel metric of PA with a growing body of literature supporting their utility given mounting evidence of CVD benefits, with trends that mirror intensity-centric metrics of PA that are used in WHO guidelines. This manuscript provides an up-to-date review of the evidence on the benefits of PA, steps, and cardiovascular outcomes.